Surrogate Motherhood: Challenges and Legal Implications - Shyamantak Misra; Prafulla Chandra Mishra (Institute of Medico-legal Publications Pvt Ltd, 2021)
Surrogacy wasn’t a commonly used term until the 21st century, it came up with the rising level of infertilityin couples and the stringent procedure of compliance for adoption. Surrogacy has always been the choice ofcouples for whom genetic link is of utmost importance. At a point of time the rate of commercial surrogacywas at its peak which leads to several issues and challenges that needs to be treated on an urgent basis andobviously an enactment to guide alongside which isn’t present till date in India. However, after the passingof the Surrogacy Regulation Bill 2019 in the Lok Sabha, a hope for betterment has arose. This piece of studyshowcases the challenges faced since time immemorial relating to Surrogacy and how it was being tackledwith, without any legislation being present in India. It also stresses on the key points of the upcoming billof 2019 and how it would prove to be a turning point for the commercial world that developed due to theSurrogacy in India.